Basic concepts for sample size calculation: Critical step for any clinical trials! - K K Gupta (Saudi Journal of Anaesthesia, 2016)
Quality of clinical trials has improved steadily over last two decades, but certain areas in trial methodology still require special attention like in sample size calculation. The sample size is one of the basic steps in planning any clinical trial and any negligence in its calculation may lead to rejection of true findings and false results may get approval. Although statisticians play a major role in sample size estimation basic knowledge regarding sample size calculation is very sparse among most of the anesthesiologists related to research including under trainee doctors. In this review, we will discuss how important sample size calculation is for research studies and the effects of underestimation or overestimation of sample size on project′s results. We have highlighted the basic concepts regarding various parameters needed to calculate the sample size along with examples.